Pemberdayaan UMKM melalui Pelatihan Aplikasi Keuangan di Desa Binaan Politeknik Negeri Lhokseumawe - Diana Diana; Mariana Mariana; Julia Alfianti; Nurul Kamaliah (LP3M IAIFA Kediri, 2025)
This community service program aimed to enhance the financial recording capacity of micro, small, and medium enterprises (MSMEs) through the use of the MitraKU digital application. The training was held on July 17, 2025, in Lhokseumawe and was attended by 20 business groups from various sectors, including food, agriculture, retail, services, and pet shops. The implementation methods included material presentation, hands-on practice, and technical assistance. The results showed that all participants successfully operated the MitraKU application independently, recorded daily transactions, and accessed basic financial reports. Initial outcomes indicated improved awareness of systematic financial recording, behavioral change in managing finances, and increased confidence in making business decisions. This success demonstrates that a simple digital application can significantly improve financial literacy among MSMEs. Further follow-up, such as regular mentoring and strengthening the role of local champions, is necessary to ensure the sustainability of this technological adoption.